2006
DOI: 10.1104/pp.106.090167
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the Arabidopsis Leaf Transcriptome Reveals Interaction of Phosphate and Sugar Metabolism

Abstract: Global gene expression was analyzed in Arabidopsis (Arabidopsis thaliana) by microarrays comprising 21,500 genes. Leaf segments derived from phosphorus (P)-starved and P-replenished plants were incubated with or without sucrose (Suc) to obtain tissues with contrasting combinations of P and carbohydrate levels. Transcript profiling revealed the influence of the two factors individually and the interactions between P-and sugar-dependent gene regulation. A large number of gene transcripts changed more than 2-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
312
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(336 citation statements)
references
References 71 publications
19
312
2
3
Order By: Relevance
“…These synergistically induced genes could be the converging points for Suc and Pi signals to regulate multiple plant responses to Pi starvation. The synergistic interaction of Suc and low-Pi signals in regulating gene expression at the genomic level has also been observed in a previous study using exogenously applied Suc to Pi-starved excised leaves (Mü ller et al, 2007). Thus, Suc appears to act as a major regulator of the expression of genes that are involved in plant responses to Pi starvation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These synergistically induced genes could be the converging points for Suc and Pi signals to regulate multiple plant responses to Pi starvation. The synergistic interaction of Suc and low-Pi signals in regulating gene expression at the genomic level has also been observed in a previous study using exogenously applied Suc to Pi-starved excised leaves (Mü ller et al, 2007). Thus, Suc appears to act as a major regulator of the expression of genes that are involved in plant responses to Pi starvation.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, the Arabidopsis pho3 mutant carries a defective copy of the SUCROSE TRANSPORTER2 (SUC2) gene, leading to substantially reduced transport of Suc from shoot to root and the suppression of induction and secretion of APase on its root surface (Zakhleniuk et al, 2001;Lloyd and Zakhleniuk, 2004). In addition, earlier studies have revealed that the expression of many genes involved in the synthesis, translocation, and degradation of Suc was altered during Pi starvation (Hammond et al, 2003;Vance et al, 2003;Wu et al, 2003;Misson et al, 2005;Mü ller et al, 2007). Furthermore, an increase in Suc biosynthesis in Pi-starved leaves has been observed in a variety of plants, including Arabidopsis, bean, barley (Hordeum vulgare), spinach (Spinacia oleracea), and soybean (Glycine max; Hammond and White, 2008).…”
mentioning
confidence: 98%
“…PPsPase1 and PECP1 are listed as strongly induced in several transcriptomics studies related to phosphate starvation (Misson et al, 2005; Bari et al, 2006;Müller et al, 2007;Thibaud et al, 2010;Hirsch et al, 2011). However, very little is known about their precise expression patterns.…”
Section: Ppspase1 and Pecp1 Are Dynamic Markers Of Pi Starvationmentioning
confidence: 99%
“…Furthermore, their corresponding mutants exhibit altered gene induction and classical Pi starvation responses, including diminished effects on Pi content and lipid remobilization (Pant et al, 2015). Candidates for the systemic control of Pi starvation responses have been proposed, including substantial transport of mRNAs throughout the plant (as reviewed in Puga et al, 2017), and the direct sensing of Pi concentration (or Pi-containing metabolites) by SPX-type proteins (Wang et al, 2009;Puga et al, 2014;Wild et al, 2016).Two phosphatases belonging to the haloacid dehalogenase (HAD) superfamily were identified as some of the most strongly induced transcripts following Pi starvation (Bari et al, 2006;Müller et al, 2007;Thibaud et al, 2010). These enzymes were named PPsPase1 (for pyrophosphatase [PPi]-specific phosphatase1) and PECP1 (for phosphoethanolamine (PEth)/ phosphocholine [PCho] phosphatase1) on the basis of their in vitro activity, following their heterologous expression in bacteria and subsequent purification (May et al, 2011(May et al, , 2012.…”
mentioning
confidence: 99%
See 1 more Smart Citation